Preparation and characterization of lignin-derived hard templated carbon(s): Statistical optimization and methyl orange adsorption isotherm studies. (December 2021) - Saini, Komal; Sahoo, Abhisek; Biswas, Bijoy; Kumar, Avnish; Bhaskar, Thallada
Graphical abstract: Highlights: Templated carbon materials were efficient for methyl orange adsorption. ZSM-5 templated showed better performance than Mordenite templated carbon. Response surface methodology optimized the adsorption parameters. Adsorption insights through isotherm, kinetics, and thermodynamic studies. Abstract: In this study, lignin-derived zeolite templated carbon materials were fabricated to remove the organic contaminant, methyl orange. Response surface methodology with Box–Behnken design was used to optimize the adsorption parameters. Based on Box–Behnken design, a quadratic model was developed to correlate the adsorption variables with the response, removal efficiency. Analysis of variance revealed the adsorbent dosage as the most influential adsorption variable. Lignin derived ZSM-5 (PZ) and mordenite (PM) templated carbon materials exhibited high surface area; 476.0 and 716.0 m 2 /g respectively. The maximum theoretical adsorption capacity of PZ and PM for methyl orange was 514.0 and 225.0 mg/g, respectively. The experimental kinetic data best fitted to pseudo-second-order model for both the adsorbents. PZ adsorbent was also utilized to treat real wastewater containing dyes and achieved 40 % methyl orange removal efficiency. Adsorption thermodynamic study revealed the process as spontaneous, exothermic and also indicated the increment in entropy after adsorption.